Aplikasi Toko Online (E-commerce) Berbasis Php dan Mysql - Rivai, Imam; , Dr. Heru Supriyono, M.Sc (2016)
Cv Arbain Jaya Mandiri Group is a company which confronts problems in marketing,where the company already has a website but do not have an online store yet, so the scope in markerting the company's products are less wide, this cause to the income obtained by the company is less of maximum. Online store aplication(e-commerce) is the solution of this problem in these aplication uses programming language PHP and MySQL database. The aplication is built using waterfall method, in still there are another phases, meanwhile for his own research uses experimental methods and qualitative approaches to test user acceptance levels of the application. Based on black box testing performed by administrator and user candidates acceptance testing is done by asking rhe respondents to try out the systems made then fill out provide questionnaire, it can be conclude that the application is running properly. The aim of this paper is to make online store application (e-commerce) where the customers cab order by online easily and quickly, so the advantage obtained by the company can be reached maximum.